2014
DOI: 10.1108/jmtm-10-2011-0099
|View full text |Cite
|
Sign up to set email alerts
|

The effects of production outsourcing on factory cost performance: an empirical study

Abstract: Access to this document was granted through an Emerald subscription provided by 353605 [] For AuthorsIf you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 83 publications
1
6
0
1
Order By: Relevance
“…Outsourcing work would reduce the labor component of COGS but increase the intermediate input component, and should not change the total appreciably. This hypothesis is consistent with the findings of Mexell,Kenyon and Westfall (2014).…”
supporting
confidence: 94%
“…Outsourcing work would reduce the labor component of COGS but increase the intermediate input component, and should not change the total appreciably. This hypothesis is consistent with the findings of Mexell,Kenyon and Westfall (2014).…”
supporting
confidence: 94%
“…We expect then that manufacturing plants would outsource production activities not only to reduce costs below in-house production, but also to improve operational performance in one or more operational areas such as first pass yield rates, equipment utilization, equipment availability, cycle times, lead-times, on-time delivery rate, or other metrics as appropriate for their respective strategies, industry, and markets. Given that earlier research found that the outsourcing of production activities did not lead to significant improvements in costs (Meixell et al 2014), we focus here instead on the overall operational effectiveness of the firm's production processes.…”
Section: 1mentioning
confidence: 99%
“…Gylling et al (2015) also found that re-shoring is occurring become of increasingly accurate cost allocation where outsourcing is concerned, and because of pressure for shorter lead-times in response to customer demands. U.S. manufacturing plants have not consistently experienced improvement in performance when outsourcing some portion of their operation (Meixell et al 2014). Some plants have improved performance (Dess et al 1995;Lei and Hitt 1995) while others have mixed or negative results in cost efficiency, productivity and profitability (Jiang et al 2006;Broedner et al 2009).…”
Section: Introductionmentioning
confidence: 98%
“…Sob esta ótica, o outsourcing das atividades de produção tem apresentado um efeito significativo sobre a forma como as indústrias de transformação e serviços têm desenvolvido seus produtos, no que tange as decisões make or buy, ou seja, produzir internamente, ou comprar de um fornecedor externo (MEIXELL; KENYON; WESTFALL, 2014). De modo que as atividades que não são competências essenciais, devem ser transferidas para terceiros, permitindo à entidade concentrar-se naquilo que ela consegue fazer com maior qualidade, produtividade e menor custo (FERRUZZI, et al 2011;MEIXELL, 2014).…”
Section: Critérios Estratégicos Para Tomada De Decisão Em Outsourcingunclassified